TRADISI PERKAWINAN SANDUNG WATANG PERSPEKTIF HUKUM ISLAM (Studi Kasus di Desa Banjarkulon Kecamatan Banjarmangu Kabupaten Banjarnegara) - Tri Setiyo Karimurrouf; Akrom Auladi (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2022)
Sandung watang consists of the word "sandung" which means stumbling and "watang" which means an obstacle. A sandung watang marriage is a marriage that is caused by an obstacle, namely the death of the parents of the prospective bride and groom between the time of the khitbah/application until the day of implementation which was agreed upon during the khitbah. In practice, a sandung watang marriage is a marriage that is carried out in front of the corpse of one of the prospective bride's parents who died before the agreed time during the khitbah/application to carry out the marriage. People affected by the sandung watang tradition are required to choose between getting married directly in front of their parents' corpses or getting married but have to wait a year after the death of their parents. So if the first choice is not implemented, it means that you are required to wait a year after the death of your parents. To make the first choice means having to postpone the funeral procession of his parents until the marriage contract is over. People who do not comply with these rules, the people of Banjarkulon Village, Banjarmangu District, Banjarnegara Regency believe that there will be calamities/disasters in the future with their household affairs. This research is a field research (field reasearch). To make it easier to find research data, the authors use the method of observation, interviews and documentation. So with this method, this research is expected to have accurate data. This research is a type of qualitative research which uses the urf approach as the analytical knife. The results of this study state that the implementation of watang watang marriages is not in harmony with fiqh qaidah and is included in the „urf fasid category because the watang watang wedding tradition is contrary to QS. An Nissa : 19, An Nissa : 59, An Nuur : 33, Al Baqarah : 233.